Incidence and factors influencing neck shortening after screw fixation of femoral neck fractures with the femoral neck system - Kai Wang; Dongze Lin; Peisheng Chen; Chaohui Lin; Tianxuan Feng; Jiajie Liu; Shunze Zheng; Yaqian Liang; Jirui Ouyang; Yubo Cui; Fengfei Lin (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective To investigate the effects of postoperative femoral neck shortening in patients with femoral neck fractures fixed with femoral neck system screws (FNS) and to explore the factors influencing femoral neck shortening. Method To retrospectively analyze the data of 113 patients with femoral neck fractures admitted to the Second Hospital of Fuzhou City, affiliated with Xiamen University, between December 2019 and January 2022. Of these, 87 patients were followed up for more than 12 months, 49 men and 38 women: 36 cases of Garden I and II fractures and 51 cases of Garden III and IV fractures, to record the patient's hip Harris score at 12 months postoperatively. Patients were divided into femoral neck shortening group and femoral neck no shortening group according to their regular postoperative follow-up radiographic measurements. To count the incidence of femoral neck shortening, a comparison of postoperative complication rates and hip Harris scores between the two groups was made. Statistical comparison of the two groups and a multifactorial logistic regression analysis were also performed to analyze the factors affecting femoral neck shortening. Results All 87 patients were followed up for more than 12 months after surgery. In 34 of these cases, neck shortening occurred, and the incidence rate was 39.1%. 15 cases of severe shortening, incidence of 17.2%; fracture healing 84 cases, fracture healing rate of 96.5%. The hip Harris score was 83.99 (81.95, 89.20) in the neck shortening group at 12 months postoperatively, 90.87 (87.95, 94.80) for the group without neck shortening; the difference between the two groups was statistically significant (P < 0.01). 32 cases of fracture healing in the neck shortening group at 12 months after surgery, fracture healing rate of 94.1%; 52 cases healed without neck shortening group, fracture healing rate of 98.1%. The difference between the two groups was not statistically significant (P = 0.337). High incidence of neck shortening after FNS fixation of femoral neck fractures, cortical comminution of the severed end, fracture fractionation and quality of reduction were significantly correlated with neck shortening. Conclusion High incidence of postoperative neck shortening after internal fixation of femoral neck fractures with the femoral neck system, the cortical comminution, the type of fracture, and the quality of fracture reduction are the influencing factors; femoral neck shortening can affect postoperative hip function, but does not affect fracture healing.